Smartphone and application use in self-management of chronic kidney disease: a cross-sectional feasibility study - Marinho, Christielle Lidianne Alencar; Gomes, Orlando Vieira; Silva Junior, Geraldo Bezerra da; Schwingel, Paulo Adriano (São Paulo Medical Journal, 2023)
INTRODUCTION: Smartphone and application use can improve communication and monitoring of chronic diseases, including chronic kidney disease, through self-management and increased adherence to treatment. OBJECTIVE: To assess smartphone use in patients with chronic kidney disease on dialysis and their willingness to use mobile applications as a disease self-management strategy. DESIGN AND SETTING: This was a cross-sectional study of chronic kidney disease patients on hemodialysis in the São Francisco Valley in the Northeast Region, Brazil. METHODS: The questionnaire developed by the authors was administered between April and June 2021. Cronbach’s alpha coefficient for the construct was 0.69. Associations between the dependent and independent variables were determined using univariate analysis. Multivariate analysis with logistic regression analysis was also performed. RESULTS: A total of 381 patients were included, of whom 64% had a smartphone, although only 3.1% knew of a kidney disease-related application. However, 59.3% believed that using an application could help them manage their disease. Having a smartphone was associated with treatment adherence, higher educational attainment, and higher per capita income. Educational attainment remained an independent factor in multivariate analysis. CONCLUSION: More than 64% of patients had a smartphone, although few knew of applications developed for kidney disease. More than half of the population believed that technology use could benefit chronic kidney disease treatment. Smartphone ownership was more common among the younger population, with higher educational attainment and income, and was associated with greater adherence to hemodialysis sessions.